The Impact of Sense of Place, form and Environment Design on Increasing the Security of Commercial Complexes - Kameli1, Mohsen; Fallah, Mehdi; AsgShahr, Niloufar Nahavandi (Ciência e Natura, 2016)
The human beings have always acted proactively in the environment and have exchanged information with it. After being located in a place and exchanging information and understanding the symbols by his senses, the human being would be able to communicate with the environment and focus his attention on it. “Sense of place” is the capability of the space or place in creating a unique sense in relation to place as a whole. Regarding the sense of place, form and environment design in commercial region which leads to easy access and high security of the place, the researchers are going to study the impact of environment design indexes on increasing the security of commercial complexes. The methodology of this research is of descriptive-analytic kind and the data have been collected through distributing questionnaires among participants.The findings of the research demonstrate that the crime opportunities which are the result of improper environment design will be reduced through employing suitable design and architecture. Furthermore, the architects have to pay more attention to the security of human being which is one the basic needs of human being and the most important index of environment quality, design an energetic space to promote the life quality and improve it and create the sense of place. Besides, through scaling the elements and ranking them, the researchers found out that compared with the environment design, the element of sense of place is in a higher rank which it causes higher security in the commercial complexes.